A pilot study of a digital ostomy leakage notification system: impact on worry and quality of life. (23rd March 2023) - Brady, Richard RW; Fellows, Jane; Meisner, Søren; Olsen, Jesper Kenneth; Vestergaard, Martin; Ajslev, Teresa Adeltoft
Abstract : Background: More than 90% of people with an ostomy worry about leakage, with associated high rates of psychological morbidity. Aims: To assess the performance of a novel digital ostomy leakage notification system in subjects with faecal stomas who experience and worry about leakage. Method: A prospective, single-arm, pilot study (ClinicalTrials.gov : NCT04894084) with 25 subjects testing the product for 21 days. Subjects completed questionnaires at baseline and termination of study evaluating leakage episodes, leakage worry and quality of life (QoL). Findings: Mean age was 56 years, 60% had an ileostomy, and 40% were females. Mean episodes of leakage outside the baseplate decreased significantly from 2.8 to 0.5 episodes after 21 days' use of the test product ( P <0.001), worry about leakage decreased significantly ( P <0.001) and QoL improved. Conclusion: The findings indicate strong improvements to emotional health with the test product, driven by reductions in leakage incidents outside baseplate and in users' worry about leakage.